Perbandingan Hasil Belajar Peserta Didik Kelas X SMA Negeri 1 Ma’rang yang Diajar melalui Model Pembelajaran Kooperatif Tipe TPS dan NHT (Studi Pada Materi Pokok Ikatan Kimia) - Sugiarti, Sugiarti; Danial, Muhammad (ChemEdu, 2021)
This study is a comparison research with quasi-experimental method aimed to investigate the differences of learning outcomes of student Class X SMA Negeri 1 Ma’rang between taught using of TPS and NHT types of cooperative learning. The study design was "Two Group, Pretest Posttest Design". The population in this study were all class X SMA Negeri 1 Ma’rang which consists of 5 classes, while the sample are class X A as experimental 1 and class X B as experimental 2 with number of students in each class is 20 people. The independent variable in this study are TPS and NHT types of cooperative learning and the dependent variable is the result of learning. Data retrieval of learning outcomes achieved by giving a pretest and posttest. Learning outcome data were analyzed using descriptive statistics and inferential statistics. The analysis showed the average value of student learning outcomes TPS class in the pretest and posttest are 35,75 and 73,70, respectively, with an average N-Gain 0,599 and NHT class, 28,25 and 79,10 with an average of 0,729 N-Gain. The results of hypothesis testing using t-test values obtained at tcount = 2,936 and α = 0.05 significance level with df = 38 obtained table = 2,036. Therefore, t count> t table, then H1 is accepted and H0 is rejected. It shows that there are difference outcomes learning of X class student of SMA Negeri 1 Ma’rang that taught by TPS and NHT types of cooperative learning model on the subject matter of the chemical bond.